(untitled) (Research, Society and Development, 2023)
Obesity is a chronic disease defined by an excessive concentration of body fat, which has been affecting more than 1 billion individuals worldwide. This disease is usually related to other metabolic disorders, such as type 2 diabetes (DM2), cardiovascular diseases (CVD), non-alcoholic fatty liver disease (NAFLD), chronic kidney disease (CKD), in addition to some types of cancer. In this perspective, this work aims to analyze studies involving Semaglutide as an anti-obesity agent, since the use of Glucagon-like peptide-1 receptor (GLP-1 RA) agonists are being indicated as one of the most positive procedures in the treatment of obesity. A systematic literature review was carried out based on articles published in the Databases Pubmed, Lilacs, Acervo +, Dove Press and in the Revista Research, Development and Society, from July 2022 to July 2023. After the filters, 41 articles remained, from which titles and abstracts were analyzed, excluding those that did not deal with the clinical perspective of the use of Semaglutide for the treatment of obesity. The 21 selected articles were submitted to a complete reading, looking for convergences and divergences in the observed results. Most articles (20) demonstrated the efficacy of semaglutide and an acceptable safety profile for its use, associated with combined and specific therapy for each patient. No increased risk from adverse effects has been reported. Semaglutide is characterized as a promising alternative in the treatment of obesity, proving to be effective in significantly reducing body weight in a sustained manner.